Consumer Perception Towards Brand Extension - Shrestha, Sajeeb Kumar (The Batuk, 2019)
This study attempts to examine consumer evaluation of brand extension in the Nepalese brand context. Major objective of the study was to how consumer perceives brand evaluation in Nepal. Two hundred convenient samples were taken in this study. Structured questionnaires were designed to collect data. Descriptive statistics and correlation analysis was used to summarize the data, to check the relation and to test the hypotheses. The research confirmed moderate correlation among brand extension with all the predictors like parent brand reputation, brand consistency, complementary features, substitutability features, transferability features, consumer innovativeness and consumer/user status.